2017
DOI: 10.1159/000477397
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Amyotrophic Lateral Sclerosis: A Case Report

Abstract: Background: Amyotrophic lateral sclerosis (ALS) is a devastating disease leading to death within 3-5 years in most cases. New approaches to treating this disease are needed. Here, we report a successful therapy. Case Report: In a 49-year-old male patient suffering from muscle weakness and fasciculations, progressive muscular atrophy, a variant of ALS, was diagnosed after extensive examinations ruling out other diseases. Due to supposed mercury exposure from residual amalgam, the patient's teeth were restored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…Interest has been rekindled in the mercury hypothesis for ALS [22] with a report of increased toenail mercury in people with ALS, possibly related to seafood consumption [23]. In addition, occasional reports have suggested that removing dental amalgam fillings, or chelation therapy, can result in stabilization or recovery from some forms of ALS [24]. We therefore sought to determine whether people with ALS are more likely than controls without ALS to be exposed to higher levels of mercury from these sources, using an online international questionnaire that gathered data on seafood and dental amalgam sources of mercury.…”
Section: Introductionmentioning
confidence: 99%
“…Interest has been rekindled in the mercury hypothesis for ALS [22] with a report of increased toenail mercury in people with ALS, possibly related to seafood consumption [23]. In addition, occasional reports have suggested that removing dental amalgam fillings, or chelation therapy, can result in stabilization or recovery from some forms of ALS [24]. We therefore sought to determine whether people with ALS are more likely than controls without ALS to be exposed to higher levels of mercury from these sources, using an online international questionnaire that gathered data on seafood and dental amalgam sources of mercury.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, an SALS patient was identified who suffered ALS due to mercury intoxication and was treated with a combination of the chelator 2,3-dimercaptopropanesulfate and a-lipoic acid for mercury cleansing that was expected to ameliorate symptoms. In fact, this case turned to be the first reported ALS cure (Mangelsdorf et al, 2017). This is reminiscent of the loss of metal homeostasis reported in Alzheimer disease, for which either Zn 2+ supplementation or Fe 3+ /Al 3+ chelation therapies have been suggested (Adlard and Bush, 2018).…”
Section: The Need For Stratification Of Als Patientsmentioning
confidence: 63%
“…Baseline studies, including complete blood count (CBC), biochemistry profile, serum electrolytes, LFTs, and RFTs test, should be carried out to assess the patient's overall health. Other specific tests include EMG, NCS, CPK levels, TFTs, autoantibody screen (ANA and ENA profile), chest X-ray, and MRI should be done in all patients who are suspected of having ALS [1,12,13]. Some investigations such as muscle biopsy, tumor markers, blood gases, viral serology, serum B12 or folate levels, genetic testing, and cerebrospinal fluid (CSF) culture should be done when needed to rule out other differentials [1].…”
Section: Discussionmentioning
confidence: 99%